B2B integrated marketing - Wilson, Chris (Henry Stewart Talks, 2008)
What is integrated marketing?, The changing landscape, Integrated planning, The situation, Objectives, Strategy, Strategy in B2B, Tactics, Action, Control, Example of building an awareness program, Where it is going: close loop marketing, Key gaps in B2B where sales and marketing are not joined up
Archived at 2022/03/17